Medicación intraconducto utilizada en retratamiento contra la bacteria Enterococcus faecalis. Revisión Bibliográfica - Campoverde Camacho, Jessica del Cisne (2022)
The purpose of endodontic therapy is to eliminate the vast majority of microorganisms present in root canals, however; chemical-mechanical preparation and irrigation is not sufficient for root canal disinfection. Therefore, intra-canal medication is essential to guarantee the success of endodontic treatment. E. faecalis is one of the bacteria present in cases of endodontic failure, so the elimination of this bacterium, a facultative anaerobe, requires an efficient antimicrobial treatment regimen. The aim of the present study was to describe the different options of intra-canal medication used in endodontic retreatment against Enterococcus faecalis bacteria. The type of study was documentary, analytical and descriptive, the type of sampling was by convenience, and a sample of 65 scientific articles in vitro and in vivo was taken from the Medline/PubMed database, Google Scholar, Scielo, Elsevier and Springer, as well as from the "Journal of Endodontics" page, and research was carried out in books and national and international repositories on the medication used in retreatment of E. faecalis. The conclusion was reached that the intra-canal medication in cases of endodontic failure due to E. Faecalis should be broad-spectrum such as triple antibiotic paste, because the microbiota in these cases is very varied. Keywords: endodoncia, Streptococcus faecalis,bacteria, reoperación, periodontitis apical.